The impact of Technetium-99m dimercapto-succinic acid scintigraphy on DNA damage and oxidative stress in children - Varol, Selcuk; Oktem, Faruk; Kocyigit, Abdurrahim; Demir, Aysegul Dogan; Karatas, Ersin; Aydin, Mehmet; Goknar, Nilufer (Wiley, 2021)
Background Technetium-99m-dimercapto succinic acid (Tc-99m DMSA) scintigraphy is a commonly used imaging modality in children with urological abnormalities. The radiopharmaceuticals, which have the effects of ionising radiation, are used in this method. This study aimed to investigate the impact of the Tc-99m DMSA scan on renal oxidative stress and mononuclear leukocyte (MNL) DNA damage. Methods Children, who were followed up by paediatric nephrology at Bezmialem Vakif University and underwent Tc-99m DMSA scintigraphy between April 2015 and January 2016 with the indication of detection of renal scars, were included in this study. The exclusion criteria were nephrolithiasis, history of premature birth and recent urinary tract infection 3 months prior to scintigraphy or antibiotic use in the last 1 month. 3 mL heparinised blood samples were obtained just before, immediately after and 1 week after the scintigraphy. MNL DNA damage, total antioxidant status (TAS) and total oxidant status (TOS) were measured in the blood samples. The oxidative stress index (OSI) was calculated. Spot urine samples were obtained from each patient before and within 3 days after performing the scintigraphy. TAS/Creatinine (TAS/Cr), TOS/Creatinine (TOS/Cr) and N-acetyl-glucosaminidase/creatinine (NAG/Cr) levels were measured in the urine samples. Results Twenty-seven children were evaluated. The values between TAS, TOS and OSI levels in serum samples at baseline, immediately after and 1 week after the scintigraphy (P = .105, P = .913, and P = .721, respectively) showed no statistically significant difference. The levels of TAS/Cr, TOS/Cr, NAG/Cr ratios and OSI, which were evaluated from urine samples before and within 3 days after the scintigraphy scan were also similar (P = .391, P = .543, P = .819 and P = .179, respectively). The levels of DNA damage only increased following scintigraphy scan and decreased a week later (P < .05). Conclusions The effect of Tc-99m DMSA scintigraphy is insufficient to create oxidative damage, but it can cause DNA damage via the direct impact of ionising radiation which can be repaired again in a short time.
Keywords: Myocardial-Perfusion Scintigraphy; Radiation-Exposure; Computed-Tomography; Ionizing-Radiation